Emotions and organizational governance - Ha<U+0308>rtel, Charmine E. J., 1959-; Ashkanasy, Neal M., 1945-; Zerbe, W. J. (Research on emotion in organizations ;, 2016)
The focus of this volume is on the role of emotions in organizational governance, which involves the complete gamut of organizational processes and procedures, including the means whereby organizations are controlled and directed. Traditionally organizational governance has been viewed as a largely procedural phenomenon, and therefore immune from the vagaries of human emotion. Nothing could be further from the truth. Organizations are structures built on human capital. As such, their governance is subject to all the vicissitudes and frailties that humans are capable of, including employee mistreatment and harm.The volume deals with such topics as governance of the workforce, the role of emotions in change and sustainability and the issues that can arise when organizational governance goes wrong. Overall, the chapters in this volume of Research on emotions in organizations demonstrate the ubiquitousness of emotions in the effects of emotions in organizational settings - starting from what goes on in the boardroom, extending right down to the way employees at the coalface interact with their customers every day.